The potentiating effect of calcitonin gene-related peptide on transient receptor potential vanilloid-1 activity and the electrophysiological responses of rat trigeminal neurons to nociceptive stimuli - Duangthip Chatchaisak; Mark Connor; Anan Srikiatkhachorn; Banthit Chetsawang (My University, 2017)
Growing evidence suggests that calcitonin gene-related peptide (CGRP) participates in trigeminal nociceptive responses. However, the role of CGRP in sensitization or desensitization of nociceptive transduction remains poorly understood. In this study, we sought to further investigate the CGRP-induced up-regulation of transient receptor potential vanilloid-1 (TRPV1) and the responses of trigeminal neurons to nociceptive stimuli. Rat trigeminal ganglion (TG) organ cultures and isolated trigeminal neurons were incubated with CGRP. An increase in TRPV1 levels was observed in CGRP-incubated TG organ cultures. CGRP potentiated capsaicin-induced increase in phosphorylated CaMKII levels in the TG organ cultures. The incubation of the trigeminal neurons with CGRP significantly increased the inward currents in response to capsaicin challenge, and this effect was inhibited by co-incubation with the CGRP receptor antagonist, BIBN4068BS or the inhibitor of protein kinase A, H-89. These findings reveal that CGRP acting on trigeminal neurons may play a significant role in facilitating cellular events that contribute to the peripheral sensitization of the TG in nociceptive transmission.
Keywords: Trigeminal ganglion; Capsaicin; Nociceptor; Pain Mechanisms and Treatments